Jesuits in the North American Colonies and the United States Faith, Conflict, Adaptation - O'Donnell, Catherine (Brill Research Perspectives in Humanities and Social Sciences, 2020)
Jesuits have shaped and been shaped by the history of the United States, from the colonial period through the contemporary era. Catherine O'Donnell explores the Society's evolving adaptation and resistance to American ideals, economic practices, and racial regimes. ; Readership: Undergraduate students studying Catholicism in the American colonies and United States or graduate students whose work touches on Catholicism and Jesuits therein, academic libraries.